Characterization of the Ends and Target Sites of the Novel Conjugative Transposon Tn5397 from Clostridium difficile: Excision and Circularization Is Mediated by the Large Resolvase, TndX - Wang, Hongmei (American Society for Microbiology, 2000)
Tn5397 is a conjugative transposon that was originally isolated from Clostridium difficile. Previous analysis had shown that the central region of Tn5397 was closely related to the conjugative transposon Tn916. However, in this work we obtained the DNA sequence of the ends of Tn5397 and showed that they are completely different to those of Tn916. Tn5397 did not contain the int and xis genes, which are required for the excision and integration of Tn916. Instead, the right end of Tn5397 contained a gene, tndX, that appears to encode a member of the large resolvase family of site-specific recombinases. TndX is closely related to the TnpX resolvase from the mobilizable but nonconjugative chloramphenicol resistance transposons, Tn4451 from Clostridium perfringens and Tn4453 from C. difficile. Like the latter elements, inserted copies of Tn5397 were flanked by a direct repeat of a GA dinucleotide. The Tn5397 target sites were also shown to contain a central GA dinucleotide. Excision of the element in C. difficile completely regenerated the original target sequence. A circular form of the transposon, in which the left and right ends of the element were separated by a GA dinucleotide, was detected by PCR in both Bacillus subtilis and C. difficile. A Tn5397 mutant in which part of tndX was deleted was constructed in B. subtilis. This mutant was nonconjugative and did not produce the circular form of Tn5397, indicating that the TndX resolvase has an essential role in the excision and transposition of Tn5397 and is thus the first example of a member of the large resolvase family of recombinases being involved in conjugative transposon mobility. Finally, we showed that introduction of Tn916 into a strain containing Tn5397 induced the loss of the latter element in 95.6% of recipients.